2013
DOI: 10.1016/j.jss.2013.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Increased efficiency of endocrine procedures performed in an ambulatory operating room

Abstract: Background-Thyroid and parathyroid procedures historically have been viewed as inpatient procedures. Due to advancements in surgical techniques, these procedures were transferred from the inpatient operating room (OR) to the outpatient OR at a single academic institution approximately seven years ago. The goal of this study is to determine whether this change has decreased turnover times and maximized OR utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…More recently, the safety and utility of outpatient thyroidectomy has been reported (1, 2426). Outpatient thyroidectomy is considered safe for most patients due to a number of advancements, including PTH testing, calcium supplementation, vocal fold evaluation and the use of intraoperative hemostatic agents and energy devices to reduce bleeding (24, 25). In keeping with the efficiency of outpatient operating centers, proper OR scheduling is essential (3).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the safety and utility of outpatient thyroidectomy has been reported (1, 2426). Outpatient thyroidectomy is considered safe for most patients due to a number of advancements, including PTH testing, calcium supplementation, vocal fold evaluation and the use of intraoperative hemostatic agents and energy devices to reduce bleeding (24, 25). In keeping with the efficiency of outpatient operating centers, proper OR scheduling is essential (3).…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to improve patient outcomes and increase centralization, thyroid surgery has been increasingly performed by high-volume surgeons (4,5,7). With economic pressures in recent years, there has also been a shift to perform more outpatient thyroid procedures, especially in healthy patients with benign disease or those requiring only thyroid lobectomy (1,3,5,6,(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Use of clinical pathways in endocrine surgery improves resource utilization and increases the value of care delivered. 12,13 Kulkarni et al 12 demonstrated that clinical pathways decreased duration of stay, costs, and charges for endocrine procedures without impacting quality of care adversely. From the same academic endocrine surgery program, Abdulla et al 13 demonstrated that transitioning appropriate operations for lesser risk surgical patients to an outpatient setting decreased cost of care.…”
Section: Discussionmentioning
confidence: 99%